MANAJEMEN LAYANAN BIMBINGAN KONSELING DI MAN PURWOREJO - Ahmad nur faizin (At-Tarbiyat, 2020)
In the development of students, guidance and counselors are needed in the education unit. Roles and instructors are considered to be a school psychologist able to provide guidance and guidance in solving various problems of students on a personal or collective scale. This problem that is often encountered by students at the high school level must be resolved through counseling at school.